Teachers’ personal beliefs on use of narratives in moral education for young children - Rahiem, Maila Dinia Husni (2016)
A qualitative approach was conducted to both explore and describe the practice and understanding of kindergarten teachers in using narratives in the teaching and learning of moral education. Participants were selected for their sensitivity, knowledge, and insight from their own personal experiences. A total of of 14 teachers were selected based on purposive sampling. The study took place in two kindergartens, one is an Islamic kindergarten located on the outskirts of Jakarta. The second kindergarten is a public kindergarten, non-faith based, which is located in South Jakarta. Both kindergartens have consistently and regularly incorporated narrative activities into the students’ curriculum, while the teachers use the method of storytelling in learning. The primary data collection method was through semi-structured, in-depth interviews and focus-group discussions. Supplementary information was collected using observation and document analysis. The themes in this study were obtained from the process of coding and categorizing themes based on the transcripts of the interviews and analysis of other documents. This study asked two main questions: how and why do kindergarten teachers use narratives in the teaching and learning of moral education for young children? The findings revealed that there are five ways that the participants in this study use narratives in the teaching and learning of moral education for young children, namely: they repeat the narrative; they give real examples; they discuss the story; they dramatize the storytelling; and they modify the story. The findings indicated three reasons that the teachers have for using narratives to educate in kindergartens, the first reason is because they believe narratives inspire children to behave prosocially. The second reason is, they believe that narratives motivate children to have good character. And the last reason is that they believe narratives are able to strengthen the childrens’ faith in God. In conclusion, the quality of moral education through the use of narratives can be improved, to make it more useful and effective, by improving the ways narratives are used and combining this with a better understanding of the objectives of moral education.